2017
DOI: 10.1556/030.64.2017.003
|View full text |Cite
|
Sign up to set email alerts
|

Study on the glutathione metabolism of the filamentous fungus Aspergillus nidulans

Abstract: Yeast protein sequence-based homology search for glutathione (GSH) metabolic enzymes and GSH transporters demonstrated that Aspergillus nidulans has a robust GSH uptake and metabolic system with several paralogous genes. In wet laboratory experiments, two key genes of GSH metabolism, gcsA, and glrA, encoding γ-L-glutamyl-L-cysteine synthetase and glutathione reductase, respectively, were deleted. The gene gcsA was essential, and the ΔgcsA mutant required GSH supplementation at considerably higher concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 47 publications
(107 reference statements)
0
14
0
Order By: Relevance
“…The sclB OE strain stressed with H 2 O 2 shows an increased trxR upregulation compared to wildtype ( Fig 10B ). glrA encodes the glutathione reductase [ 92 , 93 ], which regulation was not dependent on the presence of sclB ( S7 Fig ). The catA gene, encoding the spore-specific catalase A, is upregulated in wildtype but not induced in Δ sclB in presence of H 2 O 2 ( Fig 10B ).…”
Section: Resultsmentioning
confidence: 99%
“…The sclB OE strain stressed with H 2 O 2 shows an increased trxR upregulation compared to wildtype ( Fig 10B ). glrA encodes the glutathione reductase [ 92 , 93 ], which regulation was not dependent on the presence of sclB ( S7 Fig ). The catA gene, encoding the spore-specific catalase A, is upregulated in wildtype but not induced in Δ sclB in presence of H 2 O 2 ( Fig 10B ).…”
Section: Resultsmentioning
confidence: 99%
“…This gene group includes genes encoding known and likely antioxidant enzymes ( Aspergillus Genome Database; [47]).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the genes involved in glutathione metabolism were significantly enriched in DK of the wild strain Liu 355 compared to the cultivar strain CGMCC 5.642. A study on the glutathione metabolism in the filamentous fungus Aspergillus nidulans indicated that glutathione itself and glutathione metabolic enzymes play crucial roles in the germination of conidiospores and markedly contribute to the general stress tolerance of the fungus [52]. The high expression of genes related to glutathione metabolism in the wild strain of F. filiformis implied that the strain probably had strong environmental adaptation and it would be a potential better breeding resource.…”
Section: Discussionmentioning
confidence: 99%